Anticancer Activity of a Complex of CuII with 2‐(2‐hydroxyphenylazo)‐indole‐3/‐acetic Acid on three different Cancer Cell Lines: A Novel Feature for Azo Complexes. Issue 6 (24th February 2017) - Ganguly, Durba; Jain, Chetan Kumar; Santra, Ramesh Chandra; Roychoudhury, Susanta; Majumder, Hemanta Kumar; Mondal, Tapan Kumar; Das, Saurabh
Abstract: Toxicity of azo dyes and theirinteraction with biological systems has either been overlooked or not exploited properly. A Cu II complex of 2‐(2‐hydroxyphenylazo)‐indole‐3 / ‐acetic acid (HPIA) was synthesized to see role of metal ions on azo toxicity. It was characterized with UV‐Vis, IR, EPR, mass spectrometry, elemental and thermogravimetric analysis. Evidence suggest formation of a bis‐azo complex with stability constant logβ=12.88. DFT calculations based on spectroscopic evidence suggest 1:2::Cu II :HPIA complex. Enzyme assay on reductive cleavage of the azo bond shows complex forms less amines than HPIA. Binding of complex to DNA was similar to HPIA. As the complex restricts reduction of azo bond to toxic amines and has comparable binding with DNA it could be less cytotoxic. Cis and trans HPIA and the complex were treated to normal HEK293T cells; activity was comparable at low concentrations. When compounds were treated to human colon carcinomaHCT116 cells, ALL MOLT‐4 human leukemia cells and MCF‐7 breast cancer cells activity of the complex was better than cis or trans HPIA. The study revealed complex formation of HPIA with Cu II targets carcinoma cellsmore than HPIA. Abstract : Enzyme assay on the reductive cleavage of the azo bond in HPIA and the Cu II complex shows that the latter puts a check on the formation of toxic amines. DNA binding of the complex is almost comparable with HPIA. The complex is less toxic on normal HEK293T cells but its activity on three distinctly different cancer cells was better than HPIA. This was attributed to the conjugation of HPIA with Cu II .